E-portfolio system development for undergraduate clinical dentistry: An action research study - Greviana, Nadia; Mustika, Rita; Soemantri, Diantha (Universitas Padjadjaran, 2020)
Introduction: Higher education institutions are responsible for accommodating students to synthesise the knowledge and skills they obtained in the classroom or workplace through reflections. In the field of health professional education, the use of e-portfolio has provided an empirically validated conceptual model of integrated knowledge and learning. Therefore, it is essential to analyse the need to establish a new platform to engage stakeholders and thus ensure daily use of e-portfolio by students in undergraduate dentistry program in Indonesia. The present study was aimed to develop an e-portfolio platform based on a needs analysis and explore stakeholders’ perceptions following its implementation. Methods: The present study was a participatory action research study using a cross-sectional design with a qualitative approach that involved trainees and supervisors in an undergraduate clinical dentistry program. The study was divided into three stages: the exploration stage, the pilot study stage, and the evaluation stage of the e-portfolio platform. Data were collected using in-depth interviews and focus group discussions with stakeholders, which included faculty members and students. Data were analysed thematically. Results: The e-portfolio platform was developed according to the results of the needs analysis stage while considering stakeholders’ expectations and expected features. The results of the evaluation stage indicated a positive response from respondents. Respondents considered the e-portfolio to be very useful in students’ professional development, as it helped students to understand the content, assisted in learning, and improved their understanding of self-reflection. Conclusion: Performing a needs analysis prior to the development of an e-portfolio system provided information on technical issues regarding its development as well as the adequate supporting system required prior to its implementation. Although the implementation of the e-portfolio developed in this early stage was not conducted ideally, students reported a satisfactory impact on their learning.